A Koli band member holding a banner of a Mandal - Mumbai Archive Project Team (Jio Institute, 2024)
A band member is holding a banner of Sri Hinglay Devi Prasadhik Bhajan Mandal. Sri Krishna's divine exploits are praised through the singing of devotional bhajans and kirtans.